Atresia ani (Type IV) and agenesis of the vulva in a Gyr Calf born in Colombia: a case report - Córdoba-Parra, Juan David (2021)
Abstract A case of an imperforate Gyr calf born in a ranch is reported in Cundinamarca, Colombia. The calf was in an agonizing state, it had urinary and fecal tenesmus. Due to animal welfare conditions, euthanasia was  performed. Congenital atresia ani, agenesis of the vulva, rectovaginal fistula, urosalpinx-urometrocolpos and coprosalpinxcoprometrocolpos was present